PHYSICAL AND COMPUTER MODELING OF STRESSED STATE OF THE STEEL INGOTS AT COMBINATION (HEAT AND FORCE) LOADING - S. V. Shilko; L. P. Kuhorev (Литьë и металлургия, 2006)
The efficiency of the calculation-experimental investigation of slug, including construction of finiteelement model of representative volume of material and receiving of polarization-option picture of stresses, is shown.